Prediction of aerobic performance in distance from 1200 to 2800 M for laboratory testing with military runners - Redkva, Paulo E.; Zagatto, Alessandro M.; Gomes, Elton B.; Kalva-Filho, Carlos A.; Loures, João P.; Kaminagakura, Edson Itaru; Papoti, Marcelo [UNESP] (My University, 2012)
An analysis of different techniques for the prediction of running performance has been widely investigated to improve athletes. The purpose of this study was to evaluate the use of laboratory tests to predict running performance. The relationship between maximal oxygen consumption (VO2 max), velocity associated with VO2 max (vVO2 max), and critical velocity (CV) with 1200, 2400, and 2800 m performances. Thirteen Brazilian Army runners performed an incremental treadmill test starting at 12 km.h-1 with increments of 1 km.h-1 every 3 min until exhaustion to determine VO2 max and vVO2 max. Later, the runners ran at 100, 110, and 120% of vVO2 max to determine CV on treadmill. In addition to the laboratory test, the subjects performed three maximal runs at 1200 (P1200), 2400 (P2400), and 2800 (P2800) m on the track. Data normality was verified using the Shapiro Wilk's and Pearson correlations (P=0.05) were used to determine the relationship between the laboratory variables and the performances field test. The results showed significant correlations for P1200, P2400, and P2800 with CV (r = -0.70) and vVO2 max (r = -0.85). Based on the results of this investigation, we conclude that CV and vVO2 max determined in the laboratory can be used to predict performance in the distances studied in military runners.
Keywords: Critical velocity; Field performances; VO2 Max; vVO2 peak